Screening for Cushing’s Syndrome in an Era of Epidemic Obesity - Clutter, William E. (Mo Med, 2011)
Cushing’s syndrome is a rare cause of several very common conditions, including obesity, diabetes mellitus and hypertension. Screening tests for Cushing’s syndrome have generally high sensitivity and specificity, but if applied to unselected obese patients they have unacceptably high false positive rates. Only obese patients with more specific signs of the disorder should be screened for Cushing’s syndrome.